Politeness, Power, and Minority Leadership: A Pragmatic Analysis of Ji-Yoon Kim in The Chair - Reza Anggriyashati Adara; Tiara Haya’anisa Putri Firdaus; Welliam Hamer; Ledy Nur Lely; Nur Azmi Rohimajaya (Makassar State University, 2026)
This study analyzes the politeness strategies employed by the main character, Ji-Yoon Kim, in the Netflix series The Chair using Brown and Levinson’s (1987) politeness theory. A qualitative descriptive approach was employed, combining systematic frequency counting with contextual qualitative interpretation to examine how the character constructs social and professional relationships through language. Data were drawn from dialogue transcriptions across six episodes and analyzed through a structured content analysis procedure involving the identification, classification, and interpretation of politeness strategies. The findings reveal 78 instances of politeness strategies: 23 bald-on-record (29.49%), 30 positive politeness (38.46%), 21 negative politeness (26.92%), and 4 off-record (5.13%). Positive politeness emerges as the most dominant strategy, indicating Kim’s orientation toward solidarity-building and relational maintenance within academic and interpersonal contexts. The findings suggest that politeness functions not merely as etiquette but as a strategic communicative resource for negotiating leadership, authority, and identity in institutional settings. By examining politeness in a contemporary media narrative, this study contributes to pragmatic research on leadership discourse and identity performance in professional communication.